Effect of a Short Term Core and Lower Extremity Strengthening on the Functionality of Patients with Moderate Knee Osteoarthritis: A Comparative Trial - Deepika Lakhwan; Alka Pawalia; Shabnam Joshi; Vikram Singh Yadav (Journal of the Dow University of Health Sciences, 2023)
Objective: This study compared the effect of a short term core and lower extremity muscle strengthening program on the overall functionality of moderate knee osteoarthritis (OA) patients. Methods: This randomized trial was conducted at Department Of Physiotherapy Guru Jambheshwar University Of Science and Technology Hisar, India from May to September 2022. Both male and female participants within the age group of 40-60 years, with moderate knee OA grade II and III based on Kellgren and Laurence radiological classification were included. Subjects were divided equally into three intervention groups (hip, core and ankle strengthening exercises). The exercises were performed twice a week for a short term of 6 weeks. The outcome was functionality of moderate knee OA and to assess functionality of moderate knee OA, Knee Injuries and Osteoarthritis Scale (KOOS) and Chair stand test were measured at baseline, 3rd and 6th week of exercise. Results: Of total 66 participants, the mean age was 51.33 ± 6.42 years. After intervention at 3rd week, between-group comparison showed that hip exercise group significantly improved in symptoms (p-value <0.001) and combined KOOS scores (p-value 0.016). Comparison of difference (baseline and 6th week) in between group showed that pain, sport and recreation function, knee related quality of life (QOL), chair stand test and overall KOOS score (p-value <0.001 respectively) significantly improved in hip exercise group. Conclusion: This study revealed that hip muscle strengthening exercises are effective in short term reduction of pain, symptoms, QOL, and improving function in patients with moderate knee OA.